Land dispute resolution in Mozambique: institutions and evidence of agroforestry technology adoption - Unruh, Jon D. (International Food Policy Research Institute, 2001)
Successful adoption of natural resource management technologies requires that important fundamentals of property rights be established. Because disputes over property rights occur universally, the ability to successfully defend one's rights to property exercises a central influence on the tenure security necessary for technology adoption. However, defending rights to property rests upon the possession of evidence that is readily available and widely regarded as legitimate. This paper presents work carried out in postwar Mozambique on the availability and legitimacy of evidence pertaining to land tenure dispute resolution. What is unusual about the Mozambique case is that the physical presence of a natural resource management technology -agroforestry trees in this case - also serves as one of the most widely available and legitimate forms of evidence in the postwar period. Such an arrangement reveals important aspects about the reverse relationship between property rights and technology adoption. While such an evidence role for a technology may at first appear to encourage further adoption of agroforestry, important influences on property rights in the postwar setting serve to discourage full adoption and jeopardize the long-term presence of existing agroforestry trees. It remains to be seen if recent legislative changes regarding property rights will successfully engage customary forms of evidence and encourage full adoption of agroforestry in Mozambique.